FORMATION OF A STRATEGIC-ORIENTED MODEL OF SUSTAINABLE DEVELOPMENT OF REGIONS - Медвідь, Ганна Сергіївна (Journal of Strategic Economic Research, 2023)
The current system of strategic management cannot ensure the effective implementation of public administration functions aimed at achieving long-term goals of sustainable development of regions, so it can not completely eliminate the accumulated imbalances in socio-economic development and prevent them in the future. The formation of a strategically oriented model is important for the sustainable development of regions. Objective: To form a strategically oriented model of sustainable development of the region. Research methods: general scientific methods: analysis, synthesis, induction, deduction, systems approach and modeling – to study the theoretical issues of forming a strategically-oriented model of sustainable development of regions; generalization method – for the formation of a strategically oriented model of sustainable development of regions. The article examines the conceptual foundations of the formation of a strategically oriented model of sustainable development of regions. A conceptual strategic-oriented model of sustainable development of regions has been developed. The principles of sustainable socio-economic development management at the regional level are formulated. The directions of strategically-oriented sustainable development of the regions are offered. The comprehensive strategy for the sustainable development of regions based on a strategic-oriented model is based on the effective management of its socio-economic potential, based on the logic of "principles – process – results", integrating research methods of institutional economic theory and resource methods. The most important expected results of these measures are improving the quality of life of the population, increasing the socio-economic potential of the region, sustainable development of the entire regional socio-economic system. Further research should be devoted to the analysis of the practice of implementing the concept of sustainable development of the regions of Ukraine.